FACTORS INFLUENCING RELAPSE IN INDIVIDUALS WITH SUBSTANCE USE DISORDERS: AN ECOLOGICAL PERSPECTIVE - Ndou, Nobuhle; Khosa, Priscalia (Social Work, 2023)
Substance abuse is a global problem that has generated considerable concern among patients, families, clinicians and researchers. Existing research has not explored the views of social workers as treatment professionals but has focused on the service users and their significant others. A qualitative study was conducted to explore the factors influencing relapse in individuals with substance use disorders (SUDs) from a social work perspective. The findings revealed that various factors play a role in relapse at the different levels described from the ecological perspective. The study contributes towards the development of strategies to combat relapse and help in formulating relapse prevention programmes.